Driving rehabilitation by occupational therapists in Malaysia : what are the current practices? - Yun, Xun Chang; Hanif Farhan Mohd Rasdi; Dzalani Harun; Hui, Yuan Lau; Wen, Xin Lim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Occupational therapists have a significant role in driving rehabilitation by helping clients with disabilities to return to driving. To date, the services for driving rehabilitation are still limited in Malaysia. Furthermore, the current practice of driving rehabilitation in Malaysia is still underreported. Therefore, this study aims to assess occupational therapists’ challenges, attitudes, and skills towards driving rehabilitation, the sociodemographic differences, and associations between the developed constructs. A cross-sectional study was conducted from June to September 2020. A convenience sampling method was used to recruit 177 occupational therapists with at least one year of working experience in Malaysia. The questionnaire consists of three constructs: the challenges, attitudes, and skills related to driving rehabilitation. The content validity of the questionnaire was good (S-CVI/Ave= 0.992; S-CVI/UA= 0.950; modified kappa= 0.812 to 1.000). Based on the Exploratory Factor Analysis (EFA), three items had been deleted due to low communalities. The Cronbach’s alpha for all constructs was acceptable (Cronbach’s alpha > 0.7). Experience in practicing driving rehabilitation, workplace settings, and educational level had significant differences in at least one of the constructs. Age and years graduated had a significant positive correlation with skills. This questionnaire proved to be a tool with good content validity and reliability to assess occupational therapists’ challenges, attitudes, and skills related to driving rehabilitation. In the future, qualitative studies are recommended to better understand the occupational therapists towards driving rehabilitation, especially from their personal experience.